The coexistence of the cartesian and the sytemic thinking: the territorial limitations faced by the PAA and the PNAE in Pelotas/RS - Sodré, Maiara Tavares; Salamoni, Giancarla (Sociedade & Natureza, 2016)
The present paper approches the territorial limitations faced by the Food Acquisition Program (PAA) and by the National School Feeding Programme (PNAE) in its process of operationalisation in Pelotas from the perspective of three interviewed groups: farmers suppliers, mediating institutions and implementing entities. It adopts as its method a systemic approach, operationalized through fieldwork to conduct the interviews, which were exploited by an analysis of the content. In general it shows a tendency in each one of the three groups, that were investigated, in associate, mainly, the territorial limitations of the programs performance in the other two groups involved, minimizing the problems or difficulties recuring from its own action. While the implementing entities associate the territorial limitations essentially to suppliers, these attributes with limitations mainly from the executors. On the other hand, the intermediaries prefer to associate a share of the problems facing the purview of executors and another part to suppliers. We may infer that this trend elapses from a cartesian and fractioned vison of the world, that only sees the parts, and therefore, can not understand the complexity of reality and context that surronds and conditions the action of each individual.